Farming Systems Analysis in support of user-centered research and innovation: A joint cross-initiative collaboration - Bonilla, Camila Maria; Caulfield, Mark E.; Descheemaeker, Katrien K.; Gosh, Aniruddha; Groot, Jeroen C.J.; Zhe Guo; Hammond, James; López Ridaura, Santiago; Notenbaert, An Maria Omer; Ramírez Villegas, Julián Armando; Rosenstock, Todd S.; Steward, Peter R.; et al. (CGIAR, 2022)
Farming Systems Analysis (FSA) is commonly used in CGIAR to assess ‘what works where, and for who?’. The findings are used to prioritize tailored/context-specific interventions and target investments for greater impact. An assessment of seven new CGIAR initiatives showed us that FSA is employed in a similar way across these initiatives, open ing up avenues for strong collaboration and sharing of data, methods and results to achieve better synergies than we have done in the past.